Improving Learning Outcomes of Rhythmic Movement Activity Learning through Utilization of the TikTok Media Model Project Based Learning - Mahendra, Muh. Yusril; Mochamad Ridwan; Juheri (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Abstract This research is motivated by the lack of achievement in learning rhythmic movement activities. This is due to one of them applying a monotonous learning model and liberating students more without any special material being taught. Other factors are also the main causes, including the absence of innovative media used during the learning process, very little introduction to learning material for rhythmic movement activities, and based on diagnostics that students' understanding is still lacking regarding rhythmic movement activities. The purpose of the researchers in conducting this research was to improve learning outcomes related to cognitive and psychomotor aspects in learning rhythmic movement activities through the use of TikTok media with the model project based learning (PjBL). This research is a classroom action research (PTK) which consists of several cycles. In each cycle consists of 4 phases, namely planning, action, observation, and reflection. The results obtained show that in the first cycle, the completeness of achievement in the cognitive aspect is 53% and the psychomotor aspect is 22%. In cycle 2 the achievement of completeness in the cognitive aspect increased to 84% and the psychomotor aspect increased by 81% in all indicators